Case report and a brief review: Analysis and challenges of prenatal imaging phenotypes and genotypes in Joubert syndrome - Huang, Ling-Xi; Lu, Xian-Gui; Liu, Jiao-Xiang; Xu, Ling; Shang, Ning; Guo, Li; OuYang, Yan-Chun (Frontiers in Genetics, 2022)
Prenatal imaging phenotypes and genotypes were analyzed in 13 cases prenatally diagnosed with Joubert syndrome (JS), all of which underwent magnetic resonance imaging (MRI), ultrasound, and genetic testing. Prenatal MRI diagnosed 10 cases as JS with typical molar tooth sign (MTS), while prenatal ultrasound diagnosed or suspiciously diagnosed 11 cases as JS with typical or mild MTS in 10 cases. Mutations in JS-related genes and other prenatal JS imaging phenotypes were identified in 10 cases, including OFD1 in 2 cases [cerebellar vermis (CV) absence, posterior fossa dilation, ventriculomegaly, polydactyly, malformations of cortical development(MCD), persistent left superior vena cava, TMEM67 in 2 cases [CV absence, polydactyly, hyperechoic kidney or polycystic kidney, posterior fossa dilation, ventriculomegaly], CC2D2A in 2 cases (CV absence, polydactyly, MCD, agenesis of corpus callosum, encephalocele and hydrocephalus, ventriculomegaly, posterior fossa dilation), RPGRIP1L in 1 case (CV absence), TCTN3 in 1 case (CV absence, polydactyly, MCD and posterior fossa dilation), CEP290 in 1 case (CV absence, polycystic kidney), and NPHP1 in 1 case (CV absence). The prenatal diagnosis of JS presents a number of challenges, including the variants of unknown significance, the lack of functional assessment in prenatal imaging, unclear phenotype-genotype relationships in prenatal evaluation, and the incorrect identification of the JS hallmark, the MTS, in prenatal imaging, especially on ultrasound. Although combined MRI, ultrasound, and exome sequencing could help improve the prenatal diagnosis of JS, there still exist significant challenges.